Women’s empowerment meets gendered transformations and climate change: Lessons for resilient agri-food systems from northwest Ghana - Osei-Amponsah, Charity; Okem, Andrew; Quarmine, William (International Water Management Institute, 2023)
Women in climate-vulnerable and agriculturedependent hotspots, like the Savanna and Upper West regions in northwestern Ghana, experience diverse impacts of climate variability and change, pressures on the natural resource base, and rapid socioeconomic changes. Women’s empowerment influences their ability to build resilience against the impacts of climate change and societal transformations to sustain their agrarian livelihoods. Yet, gendered transformations are not given much attention in policymaking and climateresilience programming. The study applied the three key elements of agency, relations and structure to better understand gendered transformation, while looking at women’s empowerment through the lens of the related concepts of agency, resources and achievements. A mixed-methods approach was used to investigate the gendered nature of transformations and related issues of women’s empowerment for climate and agrifood resilience-building in 21 rural communities. The study found that women’s ability to adapt to climate change impacts, like droughts, is worsening because of cultural norms that restrict women’s control over land resources and their limited adaptive capacities. Exchange labor practices, mostly used by women, have drastically declined in the communities because agricultural production has increasingly become individualistic, mechanized, and based on nuclear households. Gendered cropping patterns have been transformed over the last 10 years. For example, while groundnut used to be produced predominantly by women, men have become the most significant groundnut producers. It is concluded that gendered transformation can enable or constrain women’s empowerment to influence their ability to build climate and agri-food resilience systems.